Fatty acid composition and physicochemical properties in kekabu seed oil - Jumat Salimon,; Khairul Asmak Abd. Kadir, (Universiti Kebangsaan Malaysia, 2005)
(Ceiba pentandra) seeds oil was solvent extracted and analyzed for its physico-chemical properties. The crude lipid content of the seeds was found up to 25 % oil yield by using soxhlet extraction while water bath orbital shaker yielded only 20 % oil. The major fatty acid components were linoleic (C18:2 n6), palmitic (C16:0), oleic (C18:1) and stearic acids (C18:0) with 42.6%,20.9%,20.8% and 13.7% of total fatty acid content respectively. Linolenic acid (CI8:3 n3) was as the minor constituent which amounted only 1.9 %. The characteristics of the oil are discussed and compared with other commercial edible oil.